PENGARUH LOKASI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN SUBSIDI MULIA GARDEN (STUDI KASUS PERUMAHAN SUBSIDI MULIA GARDEN DESA NAGA REJO) - Lestari, Ayu; Hasibuan, Melisa Zuriani (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
This study aims to determine the effect of location and product quality on purchasing decisions of Mulia Garden Subsidized Housing (Case Study of Mulia Garden Subsidized Housing in Naga Rejo Village). This study uses a quantitative descriptive approach. With a total population of 56 respondents. The sample used in this study is a saturated sample, so the number of samples obtained is 56 respondents. Data collection is done by providing a list of statements to respondents, namely to consumers of Subsidized Housing Mulia Garden, Naga Rejo Village. This study uses the technique of Multiple Linear Regression Analysis, t-test, F-test, and Coefficient of Determination. The results of multiple linear regression analysis obtained Y = 1.146 + 0.260X1 + 0.801X2. The results of the partial test (t test) show that location (X1) has a significant effect on consumer purchasing decisions. It can be seen from tcount 3,292 > ttable 1,674 with a significant 0.002 <0.05. Meanwhile, the Product Quality variable (X2) has a significant effect on Consumer Purchase Decisions. This can be seen from the value of tcount (18.702) > ttable (1.674) with a significance of 0.000 <0.05. Meanwhile, the results of the simultaneous test (f test) of the two independent variables on the dependent variable. The results showed that the location and product quality variables together had a significant influence on consumer purchasing decisions, it was seen from the value of fcount (324,256) > ftable (3.17) with a significant value of 0.000 <0.05. With an R square value of 0.924. This means that the effect of variable X1 and variable X2 on variable Y is 92.4%, while the remaining 7.6% is influenced by other variables not included in this study.